速回(a²+b²)-4a²b²=2y(x-y)²-(y-x)的三次方=(m-n)的三次方+3(n-m)²-n(m-n)²=2acd-c²a-ad²=

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/30 05:48:48
速回(a²+b²)-4a²b²=2y(x-y)²-(y-x)的三次方=(m-n)的三次方+3(n-m)²-n(m-n)²=2acd-c²a-ad²=
x͑M@# 4N`Ir@¸IfB/BAqrYy1!\W?=÷I>)2Y ntn.٭]͡G*b UWwf.AT}ޛ ڲ1Ya(*dPI,V<)Pm,)C0hOԠEûqe)|kB& J/d&&&J3g͟E+

速回(a²+b²)-4a²b²=2y(x-y)²-(y-x)的三次方=(m-n)的三次方+3(n-m)²-n(m-n)²=2acd-c²a-ad²=
速回
(a²+b²)-4a²b²=
2y(x-y)²-(y-x)的三次方=
(m-n)的三次方+3(n-m)²-n(m-n)²=
2acd-c²a-ad²=

速回(a²+b²)-4a²b²=2y(x-y)²-(y-x)的三次方=(m-n)的三次方+3(n-m)²-n(m-n)²=2acd-c²a-ad²=
1.(a²+b²)^2-4a²b²=a^4+b^4+2a^2b^2-4a^2b^2=a^4+b^4-2a^2b^2=(a^2-b^2)^2=(a+b)^2(a-b)^2
2.2y(x-y)²-(y-x)的三次方=(x-y)^2(2y-y+x)=(x-y)^2(x+y)
3.(m-n)的三次方+3(n-m)²-n(m-n)²=(m-n)^2(m-n+3-n)=(m-n)^2(m-2n+3)
4.2acd-c²a-ad²=a(2cd-c^2-d^2)=-a(c^2-2cd+d^2)=-a(c-d)^2